On the meaning of the chordophone musical instruments in the scenes of the mocking of Christ in Serbian medieval art - Gavrilović Anđela (Muzikologija, 2022)
This article examines the sacral meaning of the chordophone musical instruments in the scenes of the Mocking of Christ in Serbian medieval art (1166-1459), preserved only in two monumental ensembles - in the church of Christ Pantokrator in Dečani Monastery (1338-1339) and in the church of the Holy Archangels Gabriel and Michael in Lesnovo (1346-1347). The instruments in question are one cithara (Byzantine lyre) and one psaltery. Selected examples of the comparative material, as well as the written sources, prove that these musical instruments symbolically point to Christ’s suffering.